FLEXIBLE WORK ARRANGEMENTS IN IMPROVING THE WORK-LIFE BALANCE OF WOMEN WORKING IN PRIVATE SECTOR OF MALAYSIA: A CONCEPTUAL PAPER - Ah Tong, Sirikphon; Wong, Mikkay, Ei Leen; Cheng, Mui Li (INTI International University, 2023)
This study explores the impact of the Flexible Work Arrangement (FWAs) on the work-life balance of women employees within private sector organization. FWAs plays a key role in addressing the realities of today’s workplace for women’s work life balance. In line with this reasoning, this study examined the relationship between impacts of FWAs such as flexible work hours, remote work, and job sharing and improving women work life balance in Private sector of Malaysia. This study will identify the objectives and research questions as well as examines the relevant hypothesis which focuses on three primary factors contributing to women's work-life balance such as flexible work hours, remote work, and job sharing. At the end of the study, three hypotheses will be examined to validate the research's objectives and questions. To collect data on factors affecting women's work-life balance within specific demographic profiles. This study employs a quantitative approach that includes survey questionnaires. The research methodology involves the distribution of questionnaires to working women within the private sector in Malaysia. The study found that FWAs have a significant impact on women's work-life balance in the private sector in Malaysia. This underscores their vital role in improving the lives of career women and contributing to organizational success